2019
DOI: 10.1101/710053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centrioles control the capacity, but not the specificity, of cytotoxic T cell killing

Abstract: Immunological synapse formation between cytotoxic T lymphocytes (CTLs)and the target cells they aim to destroy is accompanied by reorientation of the CTL centrosome to a position beneath the synaptic membrane. Centrosome polarization is thought to enhance the potency and specificity of killing by driving lytic granule fusion at the synapse and thereby the release of perforin and granzymes toward the target cell. To test this model, we employed a genetic strategy to delete centrioles, the core structural compon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This behavior has long been attributed to the centrosome, which serves as a focal point for intracellular granules and polarizes toward the target cell during IS formation 2,4 . Studies from our group and others, however, indicate that the centrosome is dispensable for synaptic secretion, implying the existence of other targeting mechanisms [5][6][7] . Cytotoxic lymphocytes exert nanonewton scale forces across the IS that have been implicated in both the activation of mechanosensitive cell surface receptors and the potentiation of perforin function [8][9][10][11][12][13][14] .…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…This behavior has long been attributed to the centrosome, which serves as a focal point for intracellular granules and polarizes toward the target cell during IS formation 2,4 . Studies from our group and others, however, indicate that the centrosome is dispensable for synaptic secretion, implying the existence of other targeting mechanisms [5][6][7] . Cytotoxic lymphocytes exert nanonewton scale forces across the IS that have been implicated in both the activation of mechanosensitive cell surface receptors and the potentiation of perforin function [8][9][10][11][12][13][14] .…”
mentioning
confidence: 69%
“…That being said, our results do not exclude an important role for the centrosome and microtubules in enhancing the speed and efficiency of cytotoxic secretion. Indeed, we have shown that microtubule depletion, while failing to disrupt the directionality of degranulation, nevertheless profoundly reduces the magnitude of the secretory response 5 . Accordingly, we favor a model in which centrosome polarization delivers granules into the IS neighborhood, at which point their site of fusion is dictated by integrin licensing.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In terms of the microtubule network, re-orientation of MTOC to the immunological synapse (IS) is a hallmark for CTL activation upon recognition of target cells, which plays a key role in enriching lytic granules towards the IS (Ritter et al, 2017; Yi et al, 2013). Perturbation of the microtubule architecture in CTLs results in reduced killing efficiency but does not affect degranulation (Tamzalit et al, 2020). In our work, although the microtubule network was disrupted by nocodazole (10 μM) to a large extent, the remaining was sufficient to support lytic granule release as shown in Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%